The Effect Of Quality Of Service And Prices On Consumer Satisfaction At Klontongan Iyos Kawalu Shop, Tasikmalaya City - Jajang Hermawan; Depy Muhamad Pauzy; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the effect of service quality and price simultaneously or partially on consumer satisfaction at the Klontongan Iyos Kawalu Tasikmalaya store. The research method used is a quantitative method with a survey approach. The sample in this study amounted to 100 respondents. Data collection was done by using a questionnaire. The results of this study show that simultaneously service quality and price have a significant effect on customer satisfaction. Partially the quality of service has a significant effect on customer satisfaction. Partially, the price has a significant effect on consumer satisfaction.